Impact of Social Isolation Due to COVID-19 on Health in Older People: Mental and Physical Effects and Recommendations - Sepúlveda-Loyola, W.; Rodríguez-Sánchez, I.; Pérez-Rodríguez, P.; Ganz, F.; Torralba, R.; Oliveira, D.V.; Rodríguez-Mañas, Leocadio (The Journal of nutrition, health & aging, 2020)
To review the impact of social isolation during COVID-19 pandemic on mental and physical health of older people and the recommendations for patients, caregivers and health professionals. Narrative review. Non-institutionalized community-living people. 20.069 individuals from ten descriptive cross-sectional papers. Articles since 2019 to 2020 published on Pubmed, Scielo and Google Scholar databases with the following MeSh terms (‘COVID-19', ‘coronavirus', ‘aging', ‘older people', ‘elderly', ‘social isolation' and ‘quarantine') in English, Spanish or Portuguese were included. The studies not including people over 60 were excluded. Guidelines, recommendations, and update documents from different international organizations related to mental and physical activity were also analysed. 41 documents have been included in this narrative review, involving a total of 20.069 individuals (58% women), from Asia, Europe and America. 31 articles included recommendations and 10 addressed the impact of social distancing on mental or physical health. The main outcomes reported were anxiety, depression, poor sleep quality and physical inactivity during the isolation period. Cognitive strategies and increasing physical activity levels using apps, online videos, telehealth, are the main international recommendations. Mental and physical health in older people are negatively affected during the social distancing for COVID-19. Therefore, a multicomponent program with exercise and psychological strategies are highly recommended for this population during the confinement. Future investigations are necessary in this field.